Optimasi Keuntungan UMKM ATK (AlatTulis Kantor) Fotocopy Menggunkan Linear Programing (Studi Kasus Fotocopy Kumle) - Urrizka, Annisa; Humairoh, Arsy; Manja, Dwi Putri; Harahap, Saima Putri; Ranandia, Windi; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
Photocopy stationery stores face challenges in determining optimal prices to maximize profits while considering stock constraints, costs, and demand. This study uses a linear programming approach to solve this problem. The data used include reseller prices, selling prices, stock capacity, and market demand for seven types of goods. Validated using QM software for Windows. The results of the study indicate that this method successfully determines the optimal combination of selling price and production quantity, which provides a maximum profit of Rp910,000 per day. This approach provides a strategic solution for photocopy stationery managers in data-based decision making.